(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
One of the widespread preventable cause of unnatural death is Road Traffic Accidents. A Retrospective cross sectional study of the sociodemographic profile of pillion riders being victims of Road traffic accidents, the circumstances leading to road traffic accidents, the pattern and severity of injuries of occurring in Chennai was conducted in Saveetha Medical College and Hospital, Thandalam, Chennai, Tamilnadu. A total of 2438 cases of Road traffic accidents were recorded for a year (JAN2018-DEC2018).Out of which 62 cases (2.5%) of Road traffic accidents deals with the injuries of pillion riders. Among the pillion riders, Male outnumbered the Females(1.11 : 1). The most vulnerable age group was 21-30 years(50%). Most frequent of all is Head and Neck injuries and Injuries on the Upper limb. The information obtained can serve as a guide for better management of victims of Road traffic accidents and to establish Road safety measures.